A biologically inspired lung-on-a-chip device for the study of protein-induced lung inflammation. Issue 2 (8th December 2014) - Punde, Tushar H.; Wu, Wen-Hao; Lien, Pei-Chun; Chang, Ya-Ling; Kuo, Ping-Hsueh; Chang, Margaret Dah-Tsyr; Lee, Kang-Yun; Huang, Chien-Da; Kuo, Han-Pin; Chan, Yao-Fei; Shih, Po-Chen; Liu, Cheng-Hsien
Abstract : This study reports a biomimetic microsystem that reconstitutes the lung microenvironment for monitoring the role of eosinophil cationic protein (ECP) in lung inflammation. Abstract : This study reports a biomimetic microsystem that reconstitutes the lung microenvironment for monitoring the role of eosinophil cationic protein (ECP) in lung inflammation. ECP induces the airway epithelial cell expression of CXCL-12, which in turn stimulates the migration of fibrocytes towards the epithelium. This two-layered microfluidic system provides a feasible platform for perfusion culture, and was used in this study to reveal that the CXCL12–CXCR4 axis mediates ECP induced fibrocyte extravasation in lung inflammation. This 'lung-on-a-chip' microdevice serves as a dynamic transwell system by introducing a flow that can reconstitute the blood vessel–tissue interface for in vitro assays, enhancing pre-clinical studies. We made an attempt to develop a new microfluidic model which could not only simulate the transwell for studying cell migration, but could also study the migration in the presence of a flow mimicking the physiological conditions in the body. As blood vessels are the integral part of our body, this model gives an opportunity to study more realistic in vitro models of organs where the blood vessel i.e. flow based migration is involved.